PENGARUH PEMBERIAN KADMIUM TERHADAP TINGKAT KELANGSUNGAN HIDUP DAN KERUSAKAN STRUKTUR INSANG DAN HEPATOPANKREAS PADA UDANG REGANG [Macrobrachium sintangense (de Man)] - Agoes Soegianto; Nia Adiani Primarastri; Dwi Winarni (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
The purpose of this research was to find out the impact of cadmium on the structure of gills, hepatopancreas and on survival of shrimp. The shrimp was divided into four groups. Group I (control) was exposed to 0 ppb of cadmium, group II exposed to10 ppb of Cd, group III exposed to 20 ppb of Cd and group IV exposed to 30 ppb of Cd. Three replications were applied in each treatment. Survival rate data were collected everyday, and every two days the water was substituted with new water. The experiment was stoped when 50% of shrimps dead. The rest of shrimps were prepared for histological study. All data were subjected on Kolmogorov-Smirnov (distribution test) then continued with ANOVA test and Kruscal-Wallis tests. The result of this experiment showed that structural damage on gills and hepatopancreas increase with increasing cadmium concentration in medium. The lamella of shrimp from control group did not show hyperplasia and necrosis; in second group: 24.02% of lamella showed hyperplasia, 2.77% necrosis and 28.02% vacuolization; third group: 70.01% of lamella showed hyperplasia, 20.60% necrosis and 48.79% vacuolization; fourth group: 32.60% of lamella demonstrated hyperplasia, 57.35% necrosis and 97.50% vacuolization. Increasing the structural damage of gills and hepatopancreas, it cause the decrease on survival rate of shrimp.